A homologous recombination system to generate epitope-tagged target genes in chaetomium thermophilum: a genetic approach to investigate native thermostable proteins - Kellner, Nikola; Griesel, Sabine; Hurt, Ed (International journal of molecular sciences, 2022)
Chaetomium thermophilum is an attractive eukaryotic model organism which, due to its unusually high temperature tolerance (optimal growth at 50-52 °C), has a thermostable proteome that can be exploited for biochemical, structural and biotechnological applications. Site directed gene manipulation for the expression of labeled target genes is a desirable approach to study the structure and function of thermostable proteins and their organization in complexes, which has not been established for this thermophile yet. Here, we describe the development of a homologous recombination system to epitope-tag chromosomal genes of interest in Chaetomium thermophilum with the goal to exploit the derived thermostable fusion proteins for tandem-affinity purification. This genetic approach was facilitated by the engineering of suitable strains, in which factors of the non-homologous end-joining pathway were deleted, thereby improving the efficiency of homologous integration at specific gene loci. Following this strategy, we could demonstrate that gene tagging via homologous recombination improved the yield of purified bait proteins and co-precipitated factors, paving the way for related studies in fundamental research and industrial applications.
Published: 16 March 2022
Gesehen am 25.05.2022